i know the lim as x approaches 1 of $\displaystyle \frac{\sqrt{x+3}-\sqrt{3x+1}}{x-1}=-\frac{1}{2}$

however i don't know the steps to get there. Can someone help he? Thanks

Printable View

- Feb 11th 2009, 04:05 PMdandamanlimit question
i know the lim as x approaches 1 of $\displaystyle \frac{\sqrt{x+3}-\sqrt{3x+1}}{x-1}=-\frac{1}{2}$

however i don't know the steps to get there. Can someone help he? Thanks - Feb 11th 2009, 04:47 PMskeeter
$\displaystyle \frac{\sqrt{x+3}-\sqrt{3x+1}}{x-1} \cdot \frac{\sqrt{x+3}+\sqrt{3x+1}}{\sqrt{x+3}+\sqrt{3x+ 1}} =$

$\displaystyle \frac{(x+3) - (3x+1)}{(x-1)[\sqrt{x+3}+\sqrt{3x+1}]} =

$

$\displaystyle \frac{2(1 - x)}{(x-1)[\sqrt{x+3}+\sqrt{3x+1}]} =

$

$\displaystyle \frac{-2}{\sqrt{x+3}+\sqrt{3x+1}}$

now let $\displaystyle x \to 1$ - Feb 11th 2009, 05:55 PMdandaman
thanks man...u da man